Peranan Gen Z dalam Pengembangan Sumber Daya Manusia terhadap Efektivitas Kinerja melalui Pemanfaatan Teknologi Digital di Masyarakat - Rusli, Rusli; Manullang, Juniaty; Lukman, Apriyaldi; Cahya, Rico Dwi; Yunus, Cantika Wulandari (Al-DYAS, 2025)
The world of work has changed significantly with technological advancements, especially with the rise of Generation Z, who are the first generation to grow up in the digital age. They are highly connected and utilize technology to improve performance in the workplace. This study aims to explore the factors that influence Gen Z's participation in human resource development and how to optimize it to improve performance effectiveness. This research method uses qualitative and systematic literature review (SLR) to analyze the role of Generation Z in human resource development and performance effectiveness. This research method uses qualitative and systematic literature review (SLR) to analyze the role of Generation Z in human resource development and performance effectiveness. This research was conducted in Jogyakarta and Central Java through interviews and strengthened by 20 SINTA-indexed journals from 2020–2025. The results were obtained that their behavior and skills are important for the sustainability of the organization or work is influenced by the community, including Gen Z. Gen Z has an important role in the world of work by utilizing information technology as done by Gen Z in Central Java and Jogyakarta. They not only work to develop technology but also help the community. This shows that a holistic approach in human resource management is needed to maximize their potential. Gen Z's behavior and skills are essential to creating a productive work environment. Organizations must understand the challenges at hand and offer professional development strategies, including financial training and literacy. A good quality of work life has a positive effect on performance. Innovative HR education and good business ethics are needed to support sustainability and maximize the potential of Gen Z in the future.